What Customer Wants to Read in Your Proposal (European Journal of Marketing and Economics, 2021)
Earlier sales executives using their interpersonal - social skills built and cemented relationships with procurement officials over golf games, theatre outings and major events. That era is slowly but surely coming to an end. Today in the digital age, the context is completely different. Every organisation has access to vendors across the globe. Thanks to Artificial Intelligence (AI), organisations can compare their procurement performance in unprecedented detail. Procurement teams have relevant tools and technology to gather insights about seller’s product or service offerings to the minutest detail. However, organisations are also under constant pressure to generate value to their stakeholders on quarter-on-quarter basis. Organisations are looking towards sellers to create value to their stakeholders. Sellers should innovate and help organisations grow in multiple dimensions. Empower organisations generate value to their stakeholders. In short become their strategic partner. In this new arrangement, seller-buyer relationship is no more a transactional, order- taking and resource supplying activity. Selling process is transformed with focus on value creation. Value proposition is the core of value creation. Infact it is a disciplined concept. Sellers who use it as strategic asset create win - win situation. This research paper walks through value creation process and details how value propositions are developed.
Keywords: Hot Buttons, SMART Framework, Value Proposition, Socratic Method, Total Cost of Ownership (TCO), Total Value of Ownership (TVO). -2736850-3317113000